2016
DOI: 10.5897/ajb2016.15344
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids and amino acids contents in Scomber scombrus fillets from the South East of Tunisia

Abstract: Proximate composition, fats and amino acids of Atlantic Mackerel fillets (Scomber scombrus) from the South East of Tunisia in different seasons, were analyzed in order to assess nutritive characteristics of this species. Samples were collected monthly from Zarzis fishing port located in the South-East of Tunisia. Total fats and protein contents varied significantly (P<0.05) according to the season. The highest values were obtained in spring (11.53 and 24.1% DM, respectively). Gas chromatography analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
7
3
0
Order By: Relevance
“…Gas chromatography analysis indicated the presence of three categories of fatty acids, essentially saturated SFAs, monounsaturated MUFAs and polyunsaturated PUFAs, whose compositions varied with season. This result is in line with Guizani and Moujahed (2015) and El Oudiani et al (2016), who studdied Atlantic mackerel, and with other studies dealing with the viscera and edible parts of fish (Ben Rebah et al, 2009).…”
Section: Scomber Scombrus Fatty Acids Profilessupporting
confidence: 92%
See 3 more Smart Citations
“…Gas chromatography analysis indicated the presence of three categories of fatty acids, essentially saturated SFAs, monounsaturated MUFAs and polyunsaturated PUFAs, whose compositions varied with season. This result is in line with Guizani and Moujahed (2015) and El Oudiani et al (2016), who studdied Atlantic mackerel, and with other studies dealing with the viscera and edible parts of fish (Ben Rebah et al, 2009).…”
Section: Scomber Scombrus Fatty Acids Profilessupporting
confidence: 92%
“…In comparison with SFAs and MUFAs, PUFAs constitute the largest part of mackerel lipid muscles. This result is in accordance with Özogul et al (2007), who studied Scomber scombrus from the Marmara Sea and with Guizani and Moujahed (2015) and El Oudiani et al (2016), who studied the Atlantic mackerel from the North and South East of Tunisia. The highest PUFA levels are those of the n-3 PUFA family, mainly represented by (EPA, C20:5 n-3) and (DHA, C22:6 n-3).…”
Section: Scomber Scombrus Fatty Acids Profilessupporting
confidence: 91%
See 2 more Smart Citations
“…Suseno (2015) reported that the most abundant amino acids were glutamic acid, arginine, leucine, and lysine in tuna fish (Thunnus sp.). Salma et al (2016) found that the most abundant amino acids found in mackerel (Scomber scombrus) were glutamic acid, aspartic acid, and lysine. We did not detect any study about amino acid contents of U. moluccensis.…”
Section: Decmentioning
confidence: 99%